Growing stock volume estimation in temperate forested areas using a fusion approach with SAR satellites imagery : doctoral thesis accepted by Friedrich-Schiller University of Jena, Germany /: doctoral thesis accepted by Friedrich-Schiller University of Jena, Germany. ([2015]) - Ackermann, Nicolas
No abstract available